2021
DOI: 10.1002/ecs2.3486
|View full text |Cite
|
Sign up to set email alerts
|

High aqueous salinity does not preclude germination of invasive Iris pseudacorus from estuarine populations

Abstract: High aqueous salinity does not preclude germination of invasive Iris pseudacorus from estuarine populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…Conversely, Guppy (1912) reported that seeds of I. pseudacorus in England do not present dormancy and germinate rapidly. Our field observations align with those by Guppy (1912); during seed collections at multiple population sites in hot, early-fall conditions in California, we have observed vivipary, with a small fraction of germinated seeds within capsules while still on parent (Gillard et al, 2021). These observations suggest that some seeds lack dormancy.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Conversely, Guppy (1912) reported that seeds of I. pseudacorus in England do not present dormancy and germinate rapidly. Our field observations align with those by Guppy (1912); during seed collections at multiple population sites in hot, early-fall conditions in California, we have observed vivipary, with a small fraction of germinated seeds within capsules while still on parent (Gillard et al, 2021). These observations suggest that some seeds lack dormancy.…”
supporting
confidence: 91%
“…Therefore, in a context of global warming, it seems unlikely that increases in temperature will prevent germination or significantly decrease viability of I. pseudacorus . Furthermore, the low seed dormancy of tested populations in combination with their tolerance to high temperatures may favor a shift in the timing of germination to late summer and early fall germination in the year of seed production, including viviparous germination, which has already been observed in the field (Gillard et al, 2021). Early germination has long been considered a trait underlying the invasiveness of plant species (Pyšek and Richardson, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Germination percentages such as those found in the presence of NaCl, although low considering the high number of seeds produced, can lead to new populations established under stress conditions, as has been reported in other species. For example, in Iris pseudacorus which is invasive in California, it has been reported that even such rare events can contribute to the spread of the species in highly saline environments [ 63 ]. The importance of phenotypic plasticity in germination traits as a determinant of the success of invasive species over native species was also reported by Paudel and Battaglia [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biological invasions drive global changes in ecosystems (Vitousek, 1997 ; Mooney and Hobbs, 2000 ), which cause huge economic losses (Pimentel et al, 2000 ; Courtois et al, 2017 ) and lead to serious ecological and evolutionary consequences (Li et al, 2009 ; Ehrenfeld, 2010 ; He et al, 2020 ; Ren et al, 2021 ), including loss of biodiversity and alteration of the structure and function of the invaded ecosystem (Schirmel et al, 2016 ; Osborne and Gioria, 2018 ; Stephanie et al, 2018 ; Vaz et al, 2018 ; Giulio et al, 2022 ). Coastal wetland ecosystems are one of the habitats most vulnerable to alien species invasion (Zedler and Kercher, 2004 ; Bradley et al, 2010 ; Gillard et al, 2021 ). Spartina alterniflora Loisel.…”
Section: Introductionmentioning
confidence: 99%